Monocyte chemotactic protein‐1 inhibits chondrogenesis of synovial mesenchymal progenitor cells: An in vitro study. (28th October 2013) - Harris, Quinn; Seto, Jonathan; O'Brien, Kate; Lee, Poh S.; Kondo, Colleen; Heard, Bryan J.; Hart, David A.; Krawetz, Roman J.
Abstract: Osteoarthritis (OA) is a multifactorial, often progressive, painful disease. OA often progresses with an apparent irreversible loss of articular cartilage, exposing underlying bone, resulting in pain and loss of mobility. This cartilage loss is thought to be permanent due to ineffective repair and apparent lack of stem/progenitor cells in that tissue. However, the adjacent synovial lining and synovial fluid are abundant with mesenchymal progenitor/stem cells (synovial mesenchymal progenitor cells [sMPCs]) capable of differentiating into cartilage both in vitro and in vivo. Previous studies have demonstrated that MPCs can home to factors such as monocyte chemotactic protein 1 (MCP‐1/CCL2) expressed after injury. While MCP‐1 (and its corresponding receptors) appears to play a role in recruiting stem cells to the site of injury, in this study, we have demonstrated that MCP‐1 is upregulated in OA synovial fluid and that exposure to MCP‐1 activates sMPCs, while concurrently inhibiting these cells from undergoing chondrogenesis in vitro. Furthermore, exposure to physiological (OA knee joint synovial fluid) levels of MCP‐1 triggers changes in the transcriptome of sMPCs and prolonged exposure to the chemokine induces the expression of MCP‐1 in sMPCs, resulting in a positive feedback loop from which sMPCs cannot apparently escape. Therefore, we propose a model where MCP‐1 (normally expressed after joint injury) recruits sMPCs to the area of injury, but concurrently triggers changes in sMPC transcriptional regulation, leading to a blockage in the chondrogenic program. These results may open up new avenues of research into the lack of endogenous repair observed after articular cartilage injury and/or arthritis. Stem Cells 2013;31:2253–2265